Road Freight Quality Management in Industry 4.0: International Experience and Perspectives in Kazakhstan - DİRSEHAN, TAŞKIN (My University, 2024)
This article explores the evolution of road freight transport in the context of Industry 4.0, focusing on management practices and technological advancements in transport and logistics companies’ management information systems. By analyzing the latest international practices in road freight quality management within Industry 4.0 through regression and correlation methods, a model highlighting the significant influence of quality over price and institutional factors on the development of information and communication technology (ICT) goods exports was developed. It showcases how digital frameworks, alongside AI and big data, can enhance road freight quality in Industry 4.0, establishing a digital ecosystem for transport and logistics quality management. This study introduces a novel perspective on managing road freight transport as a digital ecosystem, offering insights into improving ICT goods exports in Kazakhstan by enhancing management information systems. It suggests a new management information system organization scheme to increase road freight quality management efficiency and ensure quality in Industry 4.0 settings.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; İktisat; Social Sciences and Humanities; Sociology; Economics; Sosyal Bilimler (Soc); Ekonomi Ve İş; Sosyal Bilimler Genel; Ekonomi; Planlama Ve Gelişim; Social Sciences (Soc); Economics & Business; Social Sciences General; Planning & Development; Gelişim; Sosyal Bilimler ve Beşeri Bilimler; Ekonomi, Ekonometri ve Finans (çeşitli); Development; Social Sciences & Humanities; Economics, Econometrics and Finance (miscellaneous); auto freight transportation in industry 4.0; digitalization transportation; ecosystems logistic services; ICT goods exports; Kazakhstan; management information systems; quality cargo transportation; quality factors in transportation